2019
DOI: 10.24931/2413-9432-2019-8-3-36-42
|View full text |Cite
|
Sign up to set email alerts
|

Photodynamic therapy of intradermal metastatic breast cancer (literature review)

Abstract: РезюмеВ последние годы во всем мире наблюдается рост заболеваемости раком молочной железы (РМЖ), причем в 20% случаев при РМЖ происходит развитие внутрикожных метастазов. Возможности хирургического и лучевого лечения внутрикожных метастазов РМЖ достаточно ограничены, а эффективность полихимиотерапии с применением стандартных схем не превышает 22-27%, при этом срок ремиссии, как правило, составляет лишь 2-3 мес. Фотодинамическая терапия (ФДТ) является перспективным методом лечения внутрикожных метастазов РМЖ. О… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…The same authors demonstrated the use of I-PDT for breast cancer last year [99]. Another recent review was focused on metastatic intradermal metastatic breast cancer [85]. The main conclusion was that PDT with sodium sinoporphyrin shows great promise to inhibit the growth of both the tumour itself and its metastases.…”
Section: Breast Cancermentioning
confidence: 99%
“…The same authors demonstrated the use of I-PDT for breast cancer last year [99]. Another recent review was focused on metastatic intradermal metastatic breast cancer [85]. The main conclusion was that PDT with sodium sinoporphyrin shows great promise to inhibit the growth of both the tumour itself and its metastases.…”
Section: Breast Cancermentioning
confidence: 99%